INCREASING STUDENTS’ VOCABULARY OF VII GRADE AT SMP N 3 TOLITOLI THROUGH WORD SEARCH PUZZLE - Firmansyah, Moh (Jurnal Madako Education, 2017)
The objective of the research is to prove whether word search puzzle can be applied to increase students’ vocabulary.. This pre-experimental study uses 33 students as a sample. They are grade VIIf of SMP N 3 Tolitoli. The procedure of this research consists of pretest, treatment, and posttest. The result of the analysis shows that word search puzzle contribute greatly to the students’ vocabulary.. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test was 76.09 while in the post-test improved up to 84.61. The data of this research are analyzed by using SPSS Program version 16.0. Then the data of both tests are analyzed by using T-test, and the result shows that the T-test value 11.818 is high than T-table value 2.037. It can be inferred that word search puzzle was very effective to increase students’ vocabulary.  Keywords:  Increasing, vocabulary, word search puzzle